Evaluating the Effects of Assignment Report Usage on Student Outcomes in an Intelligent Tutoring System: A Randomized-Encouragement Design (Journal of Educational Data Mining, 2025)
As online learning platforms become more popular and deeply integrated into education, understanding their effectiveness and what drives that effectiveness becomes increasingly important. While there is extensive prior research illustrating the benefits of intelligent tutoring systems (ITS) for student learning, there is comparatively less focus on how teachers' use of ITS impacts student outcomes. Much existing research on teachers' ITS usage relies on qualitative studies, small-scale experiments, or survey data, making it difficult to identify the causal effects of their engagement with these systems. To bridge this gap, we conducted a study using a randomized encouragement design on an online mathematics platform, where teachers were randomly assigned to one of two groups: an encouragement group or a control group. Teachers in the encouragement group received a popup prompt urging them to explore the assignment report after they created an assignment, while those in the control group did not receive any additional prompts. The study focused exclusively on teachers new to the platform, as this group was expected to be most influenced by the encouragement prompt. The findings show that viewing the assignment report did not significantly impact the percentage of students who started the next assignment or their value-added scores. However, it did lead to a notable increase in the percentage of students completing the next assignment. This effect, confirmed using the Anderson-Rubin test (which is robust against weak instruments), demonstrates a measurable causal relationship between teachers' use of assignment reports and student outcomes. Based on data from 330 teachers, this large-scale study sheds light on the causal effects of teachers engaging with ITS data on student learning and adds to the growing evidence base for effective teaching strategies in online learning environments. The pre-registration for the paper is available at https://osf.io/5u2n3/?view_only=39c4416ed9c04666885873b82c23f734, while data and code are available at https://osf.io/4nqxu/?view_only=1dcf5157005c4f82b815dad1fc67514a.